2018
DOI: 10.3897/zookeys.765.24395
|View full text |Cite
|
Sign up to set email alerts
|

Longizonitis, a new nemognathine genus from the Himalayas (Coleoptera, Meloidae)

Abstract: The new blister beetle genus Longizonitis Pan and Bologna is described. The genus is referred to the tribe Nemognathini, subfamily Nemognathinae, and its relationships are briefly discussed. It is distributed in southern China (Yunnan, SE Xizang, and probably Fujian) and India (Uttarakhand), in a transitional area between the Palaearctic and Oriental regions. The type species, Longizonitis semirubra (Pic, 1911), comb. n., is re-described and illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Although that study was extensive, 11 genera remain to be analyzed, including Longizonitis. Pan et al [6] failed to outline the definitive placement of this genus and instead observed a patchwork of similarities, including (a) with the Nemognatha lineage (which includes Palaestrida White, 1846, and some Nearctic Nemognatha Illiger, 1807, subgenera), according to its short antennomere II, a typical condition of the tribe Palaestrini and of a few Nemognathini (see also the present study); (b) with New World Zonitis, Pseudozonitis Dillon, 1952, and Gnathium Kirby, 1818, as well as some Palaearctic Zonitis species, because of the ventral sclerotized lobes of the aedeagus; (c) with the sitarine lineage due to the lack of great modification of its galeae. In contrast to the above hypotheses, the present molecular phylogenetic result shows that Longizonitis is grouped with a portion of the polyphyletic Stenoria and is quite closely related to Ctenopus Fischer von Waldheim, 1823.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although that study was extensive, 11 genera remain to be analyzed, including Longizonitis. Pan et al [6] failed to outline the definitive placement of this genus and instead observed a patchwork of similarities, including (a) with the Nemognatha lineage (which includes Palaestrida White, 1846, and some Nearctic Nemognatha Illiger, 1807, subgenera), according to its short antennomere II, a typical condition of the tribe Palaestrini and of a few Nemognathini (see also the present study); (b) with New World Zonitis, Pseudozonitis Dillon, 1952, and Gnathium Kirby, 1818, as well as some Palaearctic Zonitis species, because of the ventral sclerotized lobes of the aedeagus; (c) with the sitarine lineage due to the lack of great modification of its galeae. In contrast to the above hypotheses, the present molecular phylogenetic result shows that Longizonitis is grouped with a portion of the polyphyletic Stenoria and is quite closely related to Ctenopus Fischer von Waldheim, 1823.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical terminology used in the descriptions are the same as those in previous studies on Nemognathinae [1,6]. The body length was measured from the labrum through the apex of abdomen.…”
Section: Morphological Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Nemognathini Laporte, 1840 que pertenece a la subfamilia Nemognathinae, es la segunda tribu más diversa de la familia, contando con aproximadamente 530 especies agrupadas en 28 géneros (Pan et al 2018). En Chile esta tribu se encuentra representada por los géneros Nemognatha Illiger, 1807 y Zonitis Fabricius, 1775 (Borchman 1917).…”
Section: Introductionunclassified
“…He considered Old World elements distinct but did not detail differences, and definitions of the genus and subgenera remain unsettled (Bologna and Pinto 2002;Bologna et al 2013). Recently, one Asian and 43 Australasian species were transferred from Zonitis to other genera (Bologna et al 2013;Pan et al 2018) and it is likely that additional species will require reassignment once relationships in the Nemognathini are better understood.…”
mentioning
confidence: 99%